Keragaman Jenis Lalat Penghisap Darah Pada Kuda Sumba (Equus caballus) Di Kabupaten Sumba Timur - Tunggu Djama, Rambu Ery; Almet, Julianty; Winarso, Aji; Djungu, Dewi F.L (Jurnal Veteriner Nusantara, 2023)
Flies are a type of ectoparasites that can interfere with thecomfortable life of livestock and act as disease vectors. Thereare two types of flies, namely sucking flies and non-bloodsucking flies. Types of bloodsucking flies are Tabanus,Haematopota, Chrysops, Stomoxys, and Haematobia, whilenon-bloodsucking flies are Musca and Hydrotae. The purposeof this study was to determine the species diversity andabundance of blood-sucking flies on the Sumba Horse (Equuscaballus) located at Paulangga Farms and Paurat Farms,Kombapari Village, Katala Hamu Lingu District, East SumbaRegency. Samples of flies were collected using an insecttweezers. The flies that were caught were put into an insectkiller bottle, then identified under a microscope according to thespecies with the identification key Hadi and Soviana (2010).Furthermore, the data were analyzed descriptively using therelative abundance formula. The identification results showedthat there were 2 (two) types of blood-sucking flies namelyTabanus sp. on Paulangga farm (38.19%) and Paurat farm (0%)and Hippobosca sp. on Paulangga farm (61.81%) and PauratFarm (100%). Factors that influence to support the diversity of sucking flies are temperature, humidity, food, and breedingsites.